Impact of Product Packaging on Consumer Behavior: A Case Study of Rwenzori Bottling Company - Christine Asekenye (Uganda Christian University, 2023)
The purpose of the study was to find out the impact of product packaging on sales, taking Rwenzori bottling company as the case study. The research was guided by the following specific objectives; to find out the nature of product packaging on customer behavior and sales, to find out the impact of product packaging on consumer behavior and sales and to find out the relationship between product packaging and sales. The research employed a descriptive cross sectional research design with a quantitative method when carrying out the investigation. The general field findings on whether packaging of the company’ product is visually appealing and attractive showed that majority strongly agreed. Findings as to whether packaging creates convenience in the distribution, display the trademark of the product showed that majority strongly agreed and the correlation was moderately significant. The recommendations included that Rwenzori bottling company needed to improve on the quality of the materials they use to make mineral water. The company needs to improve on the quality of the canned products. The company needs to provide a special service for its customer especially in places where there are functions. They should provide service for collecting empty bottles and take them back to the company for recycling. The company should also improve on the box packaging of the product for easy and lasting retention, because if the products are good the companies also need to reduce on the cost of purchasing them. The research further concluded that; The company had to deploy some of the knowledge on marketing and sales from the classical conditioning theory whose primary goal is to achieve success associated with the field of psychology and the study of human behavior because it asserts that product packaging should not only focus on fixing prices but also focuses on how associations between stimuli and responses can be formed through repeated pairings leading to learned market behaviors. The research singled out the following areas of further research; evaluating the money economy and its role in boosting effective distribution of goods and services in fragmented market like in Africa, finding out the impact of yearly sales towards achieving a high level of demand of a particular company’s product and Determining the effect of the energy sources on the level of development of the private sector.
This is a dissertation.